Analisa Kapasitas Pelayanan Kegiatan Bongkar Muat Kapal Barang di Pelabuhan Maccini Baji - Firmansyah, Rahmat; Idrus, Misliah; Chaerunnisa, Andi Sitti (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
Capacity Analysis of cargo ship loading and unloading services activities at the Maccini Baji Port. This study aimed to describe the Capacity Analysis of cargo ship loading and unloading services activities at the Maccini Baji Port, (1) How Baji Maccini port productivity based on number of loading and unloading cargo, (2) Factors that affect the productivity at the port Maccini Baji, and (3) What advice and recommendations on productivity Maccini port Baji. Stages of the data analysis are: (a) Identify the relationship between the amount of cargo and truck fleet size, the amount of cargo and service time, the amount of cargo and the number of workers unloading; (b) Perform forecasting the amount of cargo to medium term; (c) Count the number of truck fleet needs, service time, and the number of workers unloading based on the equation in the first step, based on the results of load forecasting; (d) Compare the service charge using the launch system and by using a mobile crane. The results showed that, the amount of service time available for 5,610 hours/year, truck payload capacity of 49,500 tons/year, and the number of loading and unloading labor (labor) of 9,900 people/year. Projections charge in 2020 amounted to 106,632 tonnes, for the medium term (2024) amounted to 292,291, and for the long term (2029) amounted to 858,913. Total fleet needs (truck) for a long term (10 years) as many as 28,764 trucks / year.